2018
DOI: 10.1037/xap0000133
|View full text |Cite
|
Sign up to set email alerts
|

Improving self-regulated learning with a retrieval practice intervention.

Abstract: Repeated retrieval practice is a powerful learning tool for promoting long-term retention, but students use this tool ineffectively when regulating their learning. The current experiments evaluated the efficacy of a minimal intervention aimed at improving students' self-regulated use of repeated retrieval practice. Across 2 experiments, students made decisions about when to study, engage in retrieval practice, or stop learning a set of foreign language word pairs. Some students received direct instruction abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 70 publications
5
67
2
5
Order By: Relevance
“…Optimising the learning of educational materials is of critical importance to educators and students alike. Testing is one technique that has been particularly endorsed in recent years (Ariel & Karpicke, 2017;Kornell & Vaughn, 2016;Metcalfe, 2017;Pashler, Rohrer, Cepeda, & Carpenter, 2007). It is now well-established that the process of retrieving information from memory in an initial test can improve retrieval in a later test relative to simply restudying information.…”
mentioning
confidence: 99%
“…Optimising the learning of educational materials is of critical importance to educators and students alike. Testing is one technique that has been particularly endorsed in recent years (Ariel & Karpicke, 2017;Kornell & Vaughn, 2016;Metcalfe, 2017;Pashler, Rohrer, Cepeda, & Carpenter, 2007). It is now well-established that the process of retrieving information from memory in an initial test can improve retrieval in a later test relative to simply restudying information.…”
mentioning
confidence: 99%
“…Recently, with minimal instruction on how to use generative retrieval, learners developed study habits including effective and self-regulated use of generative retrieval, as well as possible changes in long-term study habits (1). Similarly, in another study, students who were given feedback on their performance with generative retrieval as a study strategy and received instruction and guidance on how to use the strategy were found to perform better at a later testing point (9).…”
Section: Discussionmentioning
confidence: 99%
“…A potential measure to motivate students to keep on working even in the distributed practice schedule could be to inform them prior to the practice phase about the positive effects of distributed practice. For example, at least in completely self-regulated learning, Ariel and Karpicke (2018) could show that informing students about the positive effect of retrieval practice resulted in higher use of this strategy. That is, increasing the metacognitive knowledge of students could motivate them to implement even practice strategies that are more challenging, a mechanism that could also help to increase the use of distributed practice.…”
Section: Discussionmentioning
confidence: 99%